Hierarchy of interpersonal synergies in basketball: a theoretical and methodological approach - Santos, Rodrigo de Miranda Monteiro (2022)
The aim of this study was to discuss and identify, theoretically and methodologically, the hierarchical levels (i.e., dyadic and collective) of defensive interpersonal synergies in basketball. We suggest that the characteristics of a task constrain the formation of synergies from the dyadic to the collective level. Consequently, identifying multi-level interpersonal synergies in team sports demands studying the formation of synergies as a task-dependent phenomenon. Likewise, we recommend that future studies address this issue and take into account the relevance of performance goals in each level (i.e., dyadic and collective) of analysis. The Uncontrolled Manifold (UCM) concept was used to determine the limits of variability of values of task elements that allow to stabilize the performance measure. The task elements were players’ positions captured by the bidimensional (x and y) coordinates. The performance goal selected for identifying the presence of interpersonal synergies in the defensive phase of play at the dyadic level was the interpersonal distance between defenders, which, it is assumed, tends to be stabilized to prevent an opponent to get near the basket. At the collective level, the performance goal selected was the distance between the team centroid – formed by the average positions of all players in the court – and the ball, whose stabilization is likely to ensure cohesion in defense. The measures proposed in the present study were adequate to describe the defensive synergistic behavior of a basketball team in a match of the regular season of the NBA, both at dyadic and collective levels. Dyadic synergies predicated on the stabilization of the interpersonal distance by two defenders were observed during the whole match. Although collective synergies were only observed in 30% of the plays, the frequency of synergies predicated on the distance between the team centroid and the ball might be related with the occurrence of more complex team defensive behaviors. No significant differences were found in the frequency or strength of synergies between two teams during an NBA match. The dyadic synergies that most contributed to the formation of collective synergies (D5 and D6, respectively) was the only aspect that significantly distinguished the defensive behavior of Team A and Team B. Nevertheless, the variables proposed in this study were capable of identifying a fair number of interpersonal synergies at both levels (i.e., dyadic and collective). Even so, further research is needed to investigate other performance variables and their association with defensive performance. Keywords: Basketball. Synergies. Uncontrolled Manifold.